EFISIENSI, EFEKTIVITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH DI KABUPATEN MANOKWARI - Mallisa, Mini Susi; Sudarwadi, Hustianto; Mamoribo, Yubelina Y. H. (Cakrawala Management Business Journal, 2023)
This research aims to determine the level of efficiency, effectiveness and contribution of Urban and Rural Land and Building Tax (PBB-P2) to Original Regional Income (PAD) revenues in Manokwari Regency in 2018-2021. The method used in this research is a quantitative descriptive approach. The results of this research conclude that the efficiency level of PBB-P2 revenue in Manokwari Regency from 2018-2021 was very efficient, then the level of effectiveness of PBB-P2 revenue in 2018-2021 experienced insignificant fluctuations or fluctuated with an average percentage of 108. 99% with very effective criteria and the level of contribution of PBB-P2 revenue to Manokwari Regency's PAD in 2018-2021 shows the criteria value is very low with an average percentage of 6.05%, the level of contribution is decreasing every year, this is because the realization of PAD is always increases every year, but the realization of PBB-P2 is fluctuating. Keywords: Land and Building Tax, Regional Original Income, Tax Contribution